A Histomorphological Study of Vesiculobullous Lesions of Skin - Rokde, Chakor Makarand; Damle, Rajshri P; Dravid, N V (Annals of Pathology and Laboratory Medicine, 2019)
Background: Vesiculobullous disorders are a complex group of disorders which continue to be an enigma. Wide variety of pathological processes can lead to development of Vesiculobullous eruptions over the body. They may occur in many dermatoses which include various inflammatory, infective, autoimmune, drug induced as well as genetic conditions. Each entity of vesiculobullous lesion has similar or confusing clinical features but different histopathological morphology. Histopathological examination is helpful in definitive diagnosis of vesiculobullous disorder which is very essential for specific treatment and an appropriate desirable outcome. Aim: To study and classify various vesiculobullous lesions of the skin in various categories. Material and Method: A prospective observational study of vesiculobullous lesions of the skin biopsies of 93 cases were received to the department of pathology over a period of 3 years. Complete clinical and relevant history was recorded. The specimens were routinely processed and haematoxylin and eosin stained slides were studied. Result: A total of 93 cases of vesiculobullous lesions of the skin were diagnosed. Among these lesions, Pemphigus vulgaris were seen in 34 (36.55%) cases, Bullous pemphigoid in 22(22.65%) cases of and spongiotic dermatosis in 14 (15.05%) cases. The maximum numbers of cases (32.25%) were in 4th to 5th decades. Conclusion: Thorough histopathological workup and clinical correlation is essential to confirm diagnosis of vesiculobullous lesions of skin.